(untitled) (Journal of Global Accounting, 2023)
The study investigates the effect of audit firm size on voluntary corporate social disclosure of selected listed manufacturing firms in Nigeria. The study employs ex-post facto design and secondary data. The population consisted of thirty seven (37) consumer and industrial goods manufacturing firms listed in the Nigerian Stock Exchange as at December, 2017. The final sample consisted of thirty (30) firms selected using purposive sampling. We applied linear regression analysis with the aid of SPSS 20.0 software for the panel data in order to determine the relationship between the variables. The study observed that firms audited by big auditing firms with international affiliations tend to have a significant high level of corporate social disclosure than others that are audited by small local audit firms. The study recommends among others that the small local audit firm should try to emulate the big auditing firms with international affiliations.